2009
DOI: 10.5735/085.046.0409
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Tree Survival: A Study Based on the Estonian Forest Research Plots Network

Abstract: This paper describes a new SAS/STAT ® procedure for fitting models to non-normal or normal data with correlations or nonconstant variability. The GLIMMIX procedure is an add-on for the SAS/STAT product in SAS ® 9.1 on the Windows platform. PROC GLIMMIX extends the SAS mixed model tools in a number of ways. For example, it• models data from non-Gaussian distributions• implements low-rank smoothing based on mixed models • provides new features for LS-means comparisons and display• enables you to use SAS programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 18 publications
1
17
0
5
Order By: Relevance
“…The next superior competition selection approach, CZR 0.4h , was simple in practice and in accordance with studies showing that, the optimal influence zone radius strongly depended on the tree's initial dimensions (D'Amato & Puettmann, 2004;Sims et al, 2009). Considering the third suitable competitor selection method, similar to several other studies, the opening angle of 50°-60° performed well (Biging & Dobbertin, 1995;Pretzsch, 2009;Oheimb et al, 2011) where bigger angles (80° and 100° in this study) mainly de-11 Analysis of Competition Between Individual Trees young stands, where the stands are usually dense, because these types of indices give more weight to trees that are closer to the subject tree.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The next superior competition selection approach, CZR 0.4h , was simple in practice and in accordance with studies showing that, the optimal influence zone radius strongly depended on the tree's initial dimensions (D'Amato & Puettmann, 2004;Sims et al, 2009). Considering the third suitable competitor selection method, similar to several other studies, the opening angle of 50°-60° performed well (Biging & Dobbertin, 1995;Pretzsch, 2009;Oheimb et al, 2011) where bigger angles (80° and 100° in this study) mainly de-11 Analysis of Competition Between Individual Trees young stands, where the stands are usually dense, because these types of indices give more weight to trees that are closer to the subject tree.…”
Section: Discussionmentioning
confidence: 91%
“…In the early stage, pioneer birches grow quite fast and vigorously (Hynynen et al, 2011), and spatial CIs explain competition effects better in dense young stands, since they account for the short distances between the neighbouring trees, that are competing for resources. In older stands, due to mortality induced by different factors, including competition (Sims et al, 2009), the number of trees decline and nonspatial CIs are adequate for competition studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on this topic in Estonia have been done by Sims et al (2009) and Laarmann et al (2009). Sims et al (2009) showed that relative height has the greatest effect on single tree survival.…”
Section: Introductionmentioning
confidence: 99%
“…Sims et al (2009) showed that relative height has the greatest effect on single tree survival. Laarmann et al (2009) analysed the share of mortality causes (game, insects, etc.)…”
Section: Introductionmentioning
confidence: 99%